Application of SWOT Analysis in Determining the Business Strategy of the Kafi Mart Cooperative, Wali Songo Islamic Boarding School - Lucky Firman Afriyansah; M. Afifudin (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study aims to analyze the application of Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis in determining the business strategy of the Kafi Mart Cooperative at the Wali Songo Sukajadi Islamic Boarding School. The study used a descriptive qualitative approach with data collection techniques including observation, structured interviews with managers, employees, students, and the surrounding community, and documentation. Data analysis utilized data reduction, data presentation, and verification. The results indicate that Kafi Mart's strengths include a captive market of students, a strategic location, support from the Islamic boarding school, and customer loyalty. The main weaknesses lie in its undigitized management system and limited product variety. Development opportunities stem from trends in the Islamic boarding school economy and business digitalization, while threats stem from competition from nearby stores and changing consumer preferences. Recommended strategies include strengthening digital management, product diversification, and improving service quality. The application of SWOT analysis has been proven to assist the cooperative in formulating a more systematic and sustainable business strategy.